Anthropometric factors in relation to risk of glioma - Little, Rebecca B. (2013)
INTRODUCTION: Increased height and greater adiposity have been linked to an increased risk of many cancer types, though few large studies have examined these associations in glioma. We examined body weight and height as potential risk factors for glioma in a large US-based case–control study. METHODS: The analysis included 1,111 glioma cases and 1,096 community controls. In a structured interview, participants reported their height and weight at 21 years of age, lowest and highest weight in adulthood, and weight 1–5 years in the past. RESULTS: Being underweight at age 21 (BMI < 18.5 kg/m(2)) was inversely associated with the risk of glioma development. This protective association was observed in both men and women, but reached statistical significance in women only (multivariate OR 0.68; 95 % CI 0.48, 0.96). When BMI at age 21 was assessed as a continuous variate, a small but significant increase in risk was observed per unit increase in kg/m(2) (OR 1.04; 95 % CI 1.02, 1.07). Adult height, recent body weight, and weight change in adulthood were not associated with glioma risk. All results were similar among never smokers and were consistent after stratifying by glioma subtype. CONCLUSION: The present data suggest that a low body weight in early adulthood is associated with a reduced risk of glioma later in life. Results are consistent with previous studies in showing no material association of glioma risk with usual adult body weight. The present study does not support any association of adult stature with glioma risk.